Pendidikan Islam dan Kebangkitan Cendekia Muslim Indonesia: Islamic Education and the Rise of Indonesian Muslim Intellectuals - Noprijon, Noprijon; Samad, Duski; Firdaus, Firdaus (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
Muslim scholars have a significant role in maintaining the condition of Islamic development and educating a strong Muslim community. The Association of Indonesian Muslim Scholars (ICMI) was established in 1990 to promote and implement Islamic values in society. This type of research involves library research to explore references about the long journey of Islamic education, the rise of Indonesian Muslim scholars (ICMI), and the function of Muslim scholars. The results of this study have shown that the development of Islamic education in Indonesia has functioned comprehensively to the remote corners of the country, its contribution is undoubted, in addition to that Islamic education and Muslim scholars have given rise to various thoughts in the midst of society and become contributors to broad thoughts related to life in Islamic society due to the birth of ICMI) including dissatisfaction of the Islamic community towards the New Order movement, the community's desire to participate in national political movements, and differences of opinion among Muslim scholars regarding the renewal of religious thought. (ICMI) serves as a forum for religious scholars to gather for discussions, exchange brilliant ideas, provide them with access to political decision-making, enhance the public's understanding of the role of religious scholars, and encourage the public to participate in national development. From the history of (ICMI)'s founding, we can learn about the urgency of religious scholars in building national civilization, collaborating with the government, preserving mass organizations in political criticism, and continuously revitalizing Islamic religious figures.